Incinerator Sebagai Solusi Efektif Kurangi Polusi Udara untuk Mewujudkan Lingkungan Hidup Sehat - Okatiyana Okatiyana; Farrel Jilal Chisan; Brimas Rijal Maulana; Ajeng Rahayuningtyas; Muhamad Saiful Rozaq; Arselin Arifina Alanis; Adelia Putri Oktavia Ramadani; Hani Putri Safira; Salsabila Poetri Dariyah; Kevin Aqila Arfa Reza (Asosiasi Riset Ilmu Kesehatan Indonesia, 2025)
Tawangsari Hamlet, Tejosari Village, Ngablak District, Magelang Regency, faces serious waste management challenges, reflected in the high daily waste production and the inactivity of waste banks post-COVID-19. To address this issue, the Tidar University Community Service Program (KKN) was implemented, aiming to improve environmental cleanliness through active community participation. This program also supports the achievement of the